School Principal Management for Improving Elementary School Teachers' Performance Through Training - Lebang, Rita; Hidayanto, Dwi Nugroho; Gede Mulawarman, Widyatmike; Warman, Warman; Dwiyono, Yudo; Akhmad, Akhmad (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2025)
The principal must have good management skills in improving teacher performance. This study aims to describe the planning, organizing, implementing and supervising carried out by the principal to improve teacher performance at the Islamic Center Elementary School in Samarinda. This study uses a qualitative approach with a case study method. Data collection techniques include observation, in-depth interviews, and documentation, with data validity tested through triangulation of sources and methods. The research findings reveal that 1) Principal planning through comprehensive identification of teacher professional development needs, designing relevant ongoing training programs, providing resources and infrastructure that support learning innovation, and formulating measurable performance targets and transparent evaluation systems 2) Organizing principal must be reflected through the application of collaborative management principles, including clear and accountable division of tasks, the formation of competent supervisory and mentor teams, and facilitating effective communication and synergistic collaboration between teachers, 3) The implementation of principal is implemented through the provision of training, application workshops, and the adoption of innovative technology-based learning models to spur teacher creativity and mastery of technology, 4) Supervision of principal is carried out through clinical supervision that focuses on development, formative evaluation of teacher performance, constructive follow-up of evaluation results, and ongoing individual coaching programs. Comprehensively, principal leadership management to improve teacher performance through training has been implemented effectively and consistently with the principles of modern education management. This study provides practical implications for the development of an effective principal leadership model in improving the quality of education at the elementary school level.